ASPEK BIOLOGI KEONG MACAN (Babylonia spirata, L) YANG TERTANGKAP DI SEKITAR PERAIRAN MUARA SEMBILANG, KECAMATAN SAMBOJA, KABUPATEN KUTAI KARTANEGARA, KALIMANTAN TIMUR - Fitria Melani; Mohammad Mustakim; Akhmad Rafi’i (Jurnal Tropical Aquatic Sciences, 2022)
Around Muara Sembilang Waters, the babylon snail population is decreasing. Efforts to manage is an alternative that can be taken in meeting local and export needs by knowing various biological aspects of which includes the relationship length and weight, condition factors, sex ratio, level of gonadal maturity (TKG), gonadal maturity index (GIC), and the ratio of the weight of the meat divided by the total weight by the IKG value. This research was conducted in October – December 2021 using jodang fishing gear. The research method used is purposive sampling. Based on the T test on all samples, the calculated T value (0.71) is smaller than T table (1.969), this indicates that the b value is significantly different from 3 where the growth of the babylon snail is negative allometric which means the length increase is faster than the increase in weight. The sex ratio of babylon snails is not balanced and is dominated by female snails. The TKG and IKG values ​​of the dominant female babylon snails were higher than the male snail. Babylon snails experienced two cycles of gonadal maturity, the first occurred in the 39.11 - 39.51 mm size group with an IKG value of 12.32% and in the 43.31 - 43.71 size group with an IKG value of 11.76%. Allegedly in this size group is the condition of the parent who is ready to experience spawning.